"A monument to suffering and to patience": The harrowing journey of Nabby Adams through breast cancer. (May 2023) - Jimenez, Rafael E.
In 1813, Abigail "Nabby" Adams, the daughter of the second president of the United States, John Adams (1797–1801), passed away from metastatic breast cancer. Her ordeal began in 1810, at age 44, when she discovered a lump in her right breast She consulted with Dr Benjamin Rush, one of the most prominent physicians of the time and a signer of the Declaration of Independence, which resulted in a recommendation for an immediate mastectomy. The surgery was performed at her parent's home in Quincy, Massachusetts, by Dr John Warren. The crude and painful nature of the surgical procedure was highly traumatic to Ms. Adams and her family. After a few months, she returned to her home in rural New York. Within a few months she began feeling generalized pain. When it was evident that her symptoms were the result of disseminated breast cancer, she returned to her parents' house, where she died on August 15, a mere 22 months after her surgery. Ms. Adams' suffering through the stark treatment was the result of a unique historical period, when the medical community had just recently dismissed Galen's paradigms, but still lacked a basic knowledge of the disease's nature or the ability to administer painless, safe surgical treatment.